Identification Of Salmonella enterica serovar Typhi Putative Virulence Factors Using A Yeast Growth Inhibition Assay - Koay, Ley Teng (2018)
Pathogenic bacteria such as Salmonella enterica serovar Typhi (S. Typhi) evade the host immune system and cause disease in their host by producing proteins known as virulence factors (VFs). When VFs are expressed in yeast Saccharomyces cerevisiae (S. cerevisiae), they have been observed to be detrimental to yeast cells (e.g. causing growth inhibition). In this sense, yeast can act as a sensitive indicator to identify VFs. There are still unidentified VFs and for those already reported, their roles in pathogenesis are still not completely understood.